Method for improving air stability of high-nickel ternary positive electrode material and application
Patent Information
- Application Number
- CN202410046258.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-11
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-01-11
AI Technical Summary
然而,这些表面修饰物质性价比低,修饰过程较为繁琐
1.本发明利用疏水的石蜡,通过特定的表面活性剂将疏水的石蜡与亲水的高镍三元正极材料桥接起来,从而将石蜡分子锚定在高镍三元正极材料表面;在高镍三元正极材料表面构筑了疏水的表面层,阻碍了电极材料与空气中水分的接触,提高材料的空气稳定性,降低了材料的存储、运输成本。
Smart Images

Figure CN117727911B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, specifically relating to a method and application for improving the air stability of high-nickel ternary cathode materials. Background Technology
[0002] Lithium-ion batteries are important energy storage devices widely used in consumer electronics, electric vehicles, and military applications. Energy density is one of the most important performance indicators of lithium-ion batteries; the higher the energy density, the more electrical energy the battery can store, and consequently, the stronger the power delivered for the same volume or weight. In lithium-ion batteries, the positive electrode material is usually composed of heavier transition metal oxides, resulting in a lower specific capacity than the negative electrode material, thus limiting the improvement of the energy density of lithium-ion batteries.
[0003] High-nickel ternary cathode materials are composed of elements such as nickel, cobalt, manganese, and lithium. Their chemical formula is LiNi. x Co y Mn 1-x-y O2 (x≥0.6) is the material with the highest energy density among the existing mainstream commercial cathode materials (lithium cobalt oxide, lithium nickel manganese oxide, lithium iron phosphate, and ternary cathode materials), and therefore has attracted widespread attention. However, the high nickel content in high-nickel ternary cathode materials leads to excessively high reactivity of lithium on the material surface, making lithium easily react with water and carbon dioxide in the air to generate residual lithium substances such as lithium carbonate and lithium hydroxide. As the storage time of high-nickel ternary cathode materials in the air increases, the amount of residual lithium substances on the surface increases, consuming surface active lithium, reducing the amount of lithium participating in the electrochemical reaction in the cathode material, and thus reducing the electrochemical performance. For example, relevant literature reports (ACS Appl. Mater. Interfaces, 2019, 11(15): 14076-14084) that LiNi 0.70 Co 0.15 Mn 0.15After 30 days of storage in air, the discharge capacity of O2 decreases significantly. Furthermore, moisture in the air increases the lithium hydroxide content on the surface of high-nickel ternary cathode materials, raising the pH level and causing gelation during the pulping process, making battery assembly impossible. Therefore, the storage, transportation, and battery assembly of high-nickel ternary cathode materials all require controlled humidity, greatly increasing the application cost. Scientists have attempted to introduce substances such as lithium cobalt oxide and PDMS onto the surface of high-nickel ternary cathode materials to improve their air stability. However, these surface modification materials are cost-effective and the modification process is cumbersome. For example, the applicant previously coated high-nickel ternary cathode materials with copper-doped poly(m-phenylene diamine), improving the hydrophobic properties and enhancing the air stability (J. Alloys Compd. 944 (2023)169264.), but the related raw materials are cost-effective, and the experimental conditions require precise control, hindering industrial application. Therefore, it is necessary to develop a simple and efficient surface modification method to isolate the influence of moisture in the air on battery materials and improve the air stability of battery materials. Summary of the Invention
[0004] This invention provides a method and application for improving the air stability of high-nickel ternary cathode materials. By using a simple immersion method, a paraffin-based material is modified onto the surface of the high-nickel ternary cathode material with a surfactant to form a hydrophobic layer, thereby reducing the influence of moisture in the air on the high-nickel ternary cathode material and improving the air stability of the material.
[0005] The technical solution of this invention is as follows: Firstly, a method for improving the air stability of high-nickel ternary cathode materials is disclosed, as follows: A high-nickel ternary cathode material, paraffin wax, and a surfactant are dispersed in an organic solvent and stirred for 1-5 hours. The mixture is then placed in air to obtain a high-nickel electrode material with high air stability. The surfactant is one of fatty alcohol polyoxyethylene ether, perfluorooctanoic acid, or perfluorooctane sulfonic acid. The surfactant can connect the hydrophilic high-nickel ternary cathode material and the hydrophobic paraffin wax molecules through intermolecular forces, fixing the hydrophobic paraffin wax molecules to the material surface and hindering the contact between the high-nickel ternary cathode material and water. This improves the air stability of the material.
[0006] Preferably, the high-nickel ternary cathode material is LiNi. x Co y M 1-x-y O2 (x≥0.6, y<0.4, M=Mn, Al, Mo, W).
[0007] Preferably, the paraffin is liquid paraffin or solid paraffin.
[0008] Preferably, the organic solvent is one of gasoline, xylene, diethyl ether, benzene, carbon tetrachloride, or chloroform.
[0009] Preferably, the mass ratio of surfactant to high-nickel ternary cathode material is 1%-3%.
[0010] Preferably, the mass ratio of paraffin wax to high-nickel ternary cathode material is 1.5%-5%.
[0011] Secondly, the application of high-nickel, high-air-stability battery materials prepared by the method in the field of batteries is disclosed.
[0012] Compared with the prior art, the present invention has the following advantages: 1. This invention utilizes hydrophobic paraffin wax and a specific surfactant to bridge the hydrophobic paraffin wax with the hydrophilic high-nickel ternary cathode material, thereby anchoring the paraffin wax molecules on the surface of the high-nickel ternary cathode material; a hydrophobic surface layer is constructed on the surface of the high-nickel ternary cathode material, which hinders the contact between the electrode material and moisture in the air, improves the air stability of the material, and reduces the storage and transportation costs of the material.
[0013] 2. The hydrophobic surface layer constructed by this invention can reduce the reaction between high-nickel ternary cathode materials and moisture in the air, reduce the consumption of active lithium in the electrode material, and effectively improve the specific capacity of the material after storage.
[0014] 3. This invention inhibits the reaction between surface active lithium and moisture in the air in high-nickel ternary cathode material, thereby suppressing the formation of residual lithium on the surface and effectively reducing the pH value of the material after storage, which is beneficial for subsequent battery assembly.
[0015] 4. This invention uses a simple soaking method, which is easy to operate, has mild conditions, and uses cost-effective raw materials, making it suitable for large-scale production. Attached Figure Description
[0016] Figure 1 This is a graph showing the contact angle test results for NCM622.
[0017] Figure 2 This is a graph showing the contact angle test results of the modified NCM622 prepared in Example 1.
[0018] Figure 3 This is a graph showing the contact angle test results of NCM622 after modification in Comparative Example 1.
[0019] Figure 4 This is a graph showing the contact angle test results of NCM622 after modification in Comparative Example 2.
[0020] Figure 5 This is a schematic diagram of the contact angles of NCM622 modified with different surfactants in Comparative Examples 3-5 and Example 2.
[0021] Figure 6 This is a schematic diagram of the contact angle of the modified NCM622 in Examples 3-5 and Comparative Example 6.
[0022] Figure 7 These are the modified NCM622 from Examples 1, 4 and Comparative Example 5, along with their XRD patterns.
[0023] Figure 8 This is a comparison chart of the cycle performance of P-NCM622, P-NCM622S, and T-NCM622S.
[0024] Figure 9 This is a TEM image of the modified NCM622 in Comparative Example 7. Detailed Implementation
[0025] The following section uses LiNi, a commonly used high-nickel ternary cathode material, as an example. 0.6 Mn 0.2 Co 0.2 The invention is further illustrated using O2 (NCM622) as an example; other high-nickel ternary cathode materials are similar. The invention is not limited to these embodiments.
[0026] First, NCM622 was prepared using a conventional co-precipitation method: 0.788 g NiSO4·H2O, 0.26 g CoSO4·H2O, and 0.253 g MnSO4·H2O were added to 30 mL of water to obtain a solution of metal sulfate; then, sodium hydroxide solution was added to adjust the pH to 11, and the mixture was stirred at 400 r / min for 4 h at 40 °C. After centrifugation, the precipitate was collected, washed with water, and dried. The obtained Ni... 0.6 Co 0.2 Mn 0.2 O2 was mixed with 0.13g LiOH and calcined at 850℃ for 10h to obtain NCM622 material.
[0027] Example 1 0.6 g NCM622, 0.006 g fatty alcohol polyoxyethylene ether (AEO-9), and 0.01 g liquid paraffin were added to 30 mL chloroform and stirred for 3 h. The modified NCM622 was obtained by centrifugation. The modified NCM622 was then placed in air for 1 h to obtain hydrophobic NCM622.
[0028] Contact angle tests were performed on unmodified NCM622 and the modified hydrophobic NCM622 of this embodiment. The results showed that unmodified NCM622 was hydrophilic. Figure 1 The modified NCM622 has a contact angle greater than 90°. Figure 2The material is hydrophobic. This indicates that the surface layer constructed by the method of the present invention can effectively change the surface properties of the high-nickel ternary cathode material and hinder the reaction between the electrode material and moisture in the air.
[0029] Comparative Example 1 0.6 g of NCM622 and 0.01 g of liquid paraffin were added to 30 mL of chloroform and stirred for 3 hours. The modified NCM622 was obtained by centrifugation. The modified NCM622 was then placed in air for 1 hour and subjected to hydrophilicity / hydrophobicity testing. In this comparative example, the contact angle of the modified material without added surfactant was less than 10°, as detailed below. Figure 3 As shown, it is evident that hydrophobic high-nickel ternary cathode materials cannot be obtained without surfactants. This further verifies the importance of surfactants in this invention; without surfactants, paraffin cannot function effectively.
[0030] Comparative Example 2 0.6 g NCM622, 0.006 g hexadecyltrimethylammonium bromide, and 0.01 g liquid paraffin were added to 30 mL chloroform and stirred for 3 h. The modified NCM622 was obtained by centrifugation. The modified NCM622 was then placed in air for 1 h and subjected to hydrophilicity / hydrophobicity testing. We found that the contact angle of the modified material with the addition of the cationic surfactant (hexadecyltrimethylammonium bromide) was less than 10°, specifically as follows... Figure 4 As shown, a hydrophobic effect cannot be achieved. This indicates that a specific surfactant is required to anchor paraffin molecules to the electrode material surface, further demonstrating the importance and uniqueness of the surfactant in this invention.
[0031] Comparative Examples 3-5 In Example 1, the fatty alcohol polyoxyethylene ether (AEO-9) was replaced with hexadecylpyridine chloride (denoted as a), sodium dodecylbenzenesulfonate (denoted as b), and monolauryl phosphate (denoted as c), respectively, to obtain modified NCM622. The modified NCM622 was placed in air for 1 hour, and the results of hydrophilicity / hydrophobicity tests were summarized. Figure 5 .
[0032] Example 2 Unlike Example 1, in this example, fatty alcohol polyoxyethylene ether was replaced with perfluorooctanoic acid (denoted as d). The resulting modified NCM622 showed the following contact angle test results: Figure 5 As shown. By Figure 5 It can be seen that, except for perfluorooctanoic acid (d), the contact angle of the final product obtained by using other surfactants (ac) is less than 90°, indicating that a hydrophobic effect cannot be achieved. This is because the surface charge and surface interaction of the high-nickel ternary cathode material make it possible for only specific surfactants to fix paraffin on its surface, thus making the surface hydrophobic.
[0033] Examples 3-4 Unlike Example 1, the amount of fatty alcohol polyoxyethylene ether (AEO-9) added in Examples 3 and 4 was 0.018 g and 0.02 g, respectively. Contact angle tests were performed on the resulting modified NCM622. Figure 6 As shown, the contact angles in Examples 3-4 are all greater than 90°, indicating that the modified NCM622 has a hydrophobic effect. The contact angle is largest when the amount of surfactant fatty alcohol polyoxyethylene ether (AEO-9) added is 0.018g (the amount of fatty alcohol polyoxyethylene ether is 3% of the electrode material), indicating that the sample prepared at this time has the best hydrophobic effect. The effect is not good when the amount of AEO-9 added is 0.02g. This may be because when the amount of fatty alcohol polyoxyethylene ether is increased, it forms micelles and cannot achieve the effect of bridging paraffin.
[0034] Example 5 Unlike Example 1, in Example 5, the amount of liquid paraffin added was 0.03g. The modified NCM622 was then subjected to a contact angle test. Figure 6 As shown, the contact angle is greater than 90°, indicating that it has certain hydrophobic properties.
[0035] Comparative Example 6 Unlike Example 1, the amount of liquid paraffin added in this comparative example was 0.036 g. The contact angle of the resulting modified NCM622 was tested. Figure 6 As shown, the contact angle is greater than 90°, indicating a certain degree of hydrophobicity.
[0036] Example 6 0.6 g of NCM622, 0.007 g of fatty alcohol polyoxyethylene ether, and 0.01 g of liquid paraffin were added to 30 mL of diethyl ether and stirred for 3 h. The modified NCM622 was obtained by centrifugation. The modified NCM622 (denoted as T-NCM622) and the unmodified material (denoted as P-NCM622) were placed in air for 60 days. The pH value of the materials after the period of time was then tested. The test procedure was as follows: 1 g of the material was placed in 10 mL of water, stirred for 0.5 h, and then allowed to stand for 0.5 h. The pH value of the system was then measured using a pH meter.
[0037] As shown in Table 1, the tests revealed that the pH value of the modified NCM622 remained almost unchanged compared to before placement, while the pH value of the unmodified NCM622 increased significantly. This indicates that the method of the present invention can effectively inhibit the reaction between the electrode material and water, suppress the formation of residual lithium on the surface, and significantly improve the air stability of the material.
[0038] Example 7 1g of NCM622, 0.011g of perfluorooctyl sulfonic acid, and 0.02g of liquid paraffin were added to carbon tetrachloride and stirred for 3 hours. The modified NCM622 was obtained by centrifugation. The modified NCM622 was then placed in air for 2 hours to obtain hydrophobic NCM622. Both the modified NCM622 (denoted as T-NCM622) and the unmodified material (denoted as P-NCM622) were placed in air for 60 days, and the pH values of the materials after air exposure were tested. The results are shown in Table 1. The pH value of T-NCM622 after air exposure was lower than that of P-NCM622 after air exposure. The pH value of T-NCM622 after air exposure was almost the same as that before air exposure, while the pH value of P-NCM622 after air exposure was significantly higher than that before air exposure. The increase in pH value is attributed to residual lithium substances on the surface produced by the reaction of NCM622 with moisture in the air. This result demonstrates that the proposed method can significantly suppress side reactions of high-nickel ternary cathode materials in air and improve the air stability of the materials.
[0039] Table 1
[0040] XRD characterization was performed on NCM622 and the modified NCM622 samples prepared in Examples 1, 4 and Comparative Example 5, respectively, as follows: Figure 7 As shown, the characteristic peaks of the material remained almost unchanged before and after modification. This indicates that the treatment process did not adversely affect the crystal structure of NCM622, demonstrating the reliability of our method.
[0041] Example 8 Electrochemical performance tests were performed on NCM622 before storage (denoted as P-NCM622), NCM622 after two months of storage (denoted as P-NCM622S), and the material prepared in Example 1 after two months of storage (denoted as T-NCM622S). The test procedure is as follows: Electrode material, conductive carbon black, and PVDF (weight ratio 8:1:1) were mixed in NMP, and the resulting slurry was coated on aluminum foil, dried, and sliced to obtain the battery positive electrode. The battery positive electrode, lithium sheet, electrolyte, and separator were assembled into a lithium-ion battery in a glove box. Charge-discharge tests were performed on it in the range of 3-4.5V, with a charge-discharge rate of 0.2C (theoretical specific capacity of 200mAh g). -1 ).like Figure 8As shown in the test results, the discharge specific capacity of P-NCM622S decreased significantly compared to P-NCM622, indicating that during storage, the active lithium in NCM622 reacted with air, consuming a large amount of active lithium and leading to a significant decrease in specific capacity. The specific capacity of T-NCM622S remained essentially unchanged, and its cycle stability was improved to some extent. This demonstrates that the method of this invention can significantly improve the electrochemical performance of high-nickel ternary cathode materials after storage and enhance their air stability.
[0042] Example 9 A lithium-ion battery was assembled using the method described in Example 8, with the modified NCM622 prepared in Example 2 as the electrode material. Battery performance testing showed a discharge specific capacity of 173.5 mAh g⁻¹. -1 The capacity was almost identical to that of NCM-622 tested in Example 8, indicating that the coating environment does not adversely affect the capacity of the electrode material.
[0043] Example 10 Unlike Example 9, this example uses the modified NCM622 prepared in Example 3 for battery performance testing, and the discharge specific capacity is 172.4 mAhg. -1 This indicates that an appropriate amount of surfactant will not affect the discharge specific capacity of the electrode material.
[0044] Comparative Example 7 Unlike Example 8, this comparative example uses the modified NCM622 prepared in Comparative Example 5 for battery performance testing, and the discharge specific capacity is 164.6 mAhg. -1 The initial specific capacity decreased significantly. Transmission electron microscopy characterization revealed that most of the electrode material was encapsulated in paraffin wax. Figure 9 This confirms our hypothesis.
[0045] Although the present invention has been described in detail with reference to the accompanying drawings and preferred embodiments, the invention is not limited thereto. Various equivalent modifications or substitutions can be made to the embodiments of the invention by those skilled in the art without departing from the spirit and essence of the invention, and such modifications or substitutions should all be within the scope of the invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A method for improving the air stability of high-nickel ternary cathode materials, characterized in that, Specifically as follows: High-nickel ternary cathode material, paraffin, and surfactant are dispersed in an organic solvent, stirred for 1-5 hours, and then placed in air to obtain a high-nickel electrode material with high air stability. The surfactant is one of fatty alcohol polyoxyethylene ether, perfluorooctanoic acid, or perfluorooctanesulfonic acid. The paraffin wax is either liquid paraffin wax or solid paraffin wax; The organic solvent is one of gasoline, xylene, diethyl ether, benzene, carbon tetrachloride, or chloroform; The mass ratio of surfactant to high-nickel ternary cathode material is 1%-3%; The mass ratio of paraffin wax to high-nickel ternary cathode material is 1.5%-5%.
2. The method for improving the air stability of high-nickel ternary cathode materials as described in claim 1, characterized in that, The high-nickel ternary cathode material is LiNi. x Co y M 1-x-y O2 (x≥0.6, y<0.4, M=Mn, Al, Mo, W).
3. The application of high-nickel, high-air-stability battery materials prepared by any one of claims 1-2 in the field of batteries.
